Pengembangan e-modul bibliotherapy untuk mencegah stres pada ibu muda - Juwita, Ulandari; Ifdil, Ifdil (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This study aims to produce a bibliotherapy e-module to prevent stress in young mothers. The research method used is the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The initial research subjects were 126 young mothers in Koto Baru District of Sungai Penuh City with purposive sampling. The research instrument used is the Parental Stress Scale (PSS) adapted to the Indonesian version. The e-module will be validated by 3 counseling experts for content and 2 IT experts for appearance or design, as well as a small group trial of 9 young mothers. Data were analyzed descriptively. The results showed that the developed e-module prototype is applicable to be used independently by young mothers to prevent stress.